2020
DOI: 10.1111/lam.13378
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and antibiotic resistance patterns of Campylobacter fetus subsp. venerealis from cattle farms in India

Abstract: Significance and Impact of the Study: Campylobacter fetus subsp. venerealis (Cfv) is frequently associated with lowered fertility and abortion in ruminants. These infections are responsible for significant reproductive wastage in infected beef and dairy herds and may reduce gross profit margins up to 66%. In India, decreased fertility rates in productive animals are traditionally attributed to brucellosis. However, recently there has been an increase in Brucella-negative abortions both in organized and unorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, a higher‐level prevalence of C. fetus was also documented in cattle in Brazil (Miranda, 2005 ; Pellegrin et al., 2002 ; Rocha et al., 2009 ). A study conducted in India confirmed a high prevalence of C. fetus positive status as 47·6%, 3·3% and 25% from of vaginal swabs, preputial wash and cervicovaginal mucous samples, respectively collected from cows and bulls (Ishtifaq et al., 2020 ). The reported variations in Campylobacter occurrence in different countries are likely related to diverse farm management practices (de Oliveira et al., 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, a higher‐level prevalence of C. fetus was also documented in cattle in Brazil (Miranda, 2005 ; Pellegrin et al., 2002 ; Rocha et al., 2009 ). A study conducted in India confirmed a high prevalence of C. fetus positive status as 47·6%, 3·3% and 25% from of vaginal swabs, preputial wash and cervicovaginal mucous samples, respectively collected from cows and bulls (Ishtifaq et al., 2020 ). The reported variations in Campylobacter occurrence in different countries are likely related to diverse farm management practices (de Oliveira et al., 2015 ).…”
Section: Discussionmentioning
confidence: 92%
“…19 In the past few years, several reports on the high prevalence of drug-resistant Salmonella, Campylobacter spp., and Staphylococcus aureus in animals, farms, poultry markets, dairy/dairy products, street foods, etc., in India and the Indian subcontinent have been published. 3,[20][21][22][23][24][25][26][27][28][29][30] In addition to hygiene measures and vaccination, the use of phages as an antibiotic substitute to decrease the amount of Salmonella and Campylobacter entering the food chain is gaining traction across the world. A company in India (Proteon Pharmaceuticals) has made a commercially available lineup of three phage cocktails.…”
Section: Poultry Bacterial Pathogensmentioning
confidence: 99%
“…Moreover, another subspecies of C. fetus , C. fetus subsp. fetus ( Cff ) colonizes the intestinal tract of ruminants and occasionally the preputial cavity, causing sporadic abortion in cattle [ 7 , 12 ]. The correct identification of Cfv and Cff is crucial for the implementation of effective BGC control and eradication programmes.…”
Section: Introductionmentioning
confidence: 99%